History of Mathematics in High School: a proposal for didactic material based on (and despite) the Common Core - Daniel Fernandes Jelin; Antonio Luís Venezuela (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
This article examines the notorious contrast between the importance given in and outside the classroom to the use of History of Mathematics in teaching Mathematics. Based on that, we propose a framework of didactic material that encourages the use of historical elements in the fulfillment of the Brazilian Common Core for High School (BNCC-EM). The material consists of a historical recount, related to certain skill, and mathematical tasks inspired by it. We also present one example supported by three seminal contributions from the 17th century, due to Michael van Langren, Christiaan Huygens, and Edmond Halley. Throughout recount and tasks, we emphasize the use of History of Mathematics for the study of mathematical procedures and concepts, about which the BNCC-EM itself, contrary to previous milestones in Education, says nothing